Pembangunan Sistem Inventaris Gudang Pada Sekolah Menengah Kejuruan Negeri 3 Pacitan - Herwiatmoko, Richo Deska; Purnama, Bambang Eka; Wardati, Indah Uly (Speed - Indonesian Journal on Computer Science, 2014)
ABSTRACT: SMK Negeri 3 pacitan is a school that is located in the Village District Ploso pacitan lined with SMA Negeri 1 Pacitan and SMK Negeri 1 Pacitan. Distance from city to SMK Negeri 3 Pacitan journey is only about 2 km. One of the systems needed at SMK Negeri 3 Pacitan is Warehouse Inventory System. The inventory system refers to the income and expenditure activities at SMK Negeri 3 Pacitan warehouse. The system is made with a single user system and using Microsoft Visual Basic. Net, Microsoft Office Access 2003 and Windows XP as the operating system. The system includes a data inventory and distribution of incoming goods .. With a system as above, Pacitan SMK Negeri 3 is expected to assist the processing of inventory in the warehouse SMK Negeri 3 Pacitan who use computers as a primary tool properly and on time. Keywords: Inventory System Abstraksi : SMK Negeri 3 pacitan merupakan sekolah yang terletak di Kelurahan Ploso Kabupaten pacitan yang berjajar dengan SMA Negeri 1 Pacitan dan SMK Negeri 1 Pacitan. Jarak Dari kota ke SMK Negeri 3 Pacitan menempuh perjalanan hanya sekitar 2 km. Salah satu sistem yang dibutuhkan pada SMK Negeri 3 Pacitan adalah Sistem Inventaris Gudang. Sistem inventaris ini mengacu pada kegiatan pemasukan dan pengeluaran barang pada gudang SMK Negeri 3 Pacitan. Sistem ini dibuat dengan sistem satu user dan menggunakan Microsoft Visual Basic.Net, Microsoft Office Access 2003 dan Windows XP sebagai operasi sistemnya. Sistem ini meliputi data inventaris barang masuk dan pendistribusian.. Dengan sistem seperti diatas, SMK Negeri 3 Pacitan diharapkan dapat membantu proses pengolahan inventaris pada gudang SMK Negeri 3 Pacitan yang menggunakan komputer sebagai alat bantu utama dengan baik dan tepat waktu. Kata kunci :Â  Sistem Inventaris Gudang